A Study on Design of Microgrid(MG) Optimal Operation Algorithm for Development of Semi-Wheel System - Yeo, Seo-Hyun; Park, Jin-Wook; Na, Jeong-Sueng; Park, Seong-Mi; Park, Sung-Jun (International Journal of Engineering and Technology, 2018)
Background/Objectives: Recently, due to the change of power paradigm, interest in MG(Microgrid) is increasing. However, the realization of MG requires very sophisticated algorithms. Therefore, before implementation, we want to develop a virtual MG operation system that can verify economical & efficient feasibility.Methods/Statistical analysis: In this paper, we design MG optimal operation algorithm as the first step for the development of Semi-Wheel-System. The design method is to analyze the MG components in the Geocha island. Especially, the fuel consumption per diesel generator output and characteristics of BESS battery are analyzed. Matlab, SPSS is used to apply the curve fitting technique and trend prediction.Findings: As a result of designing the optimal operation algorithm that MG can operate most efficiently, the diesel generator is controlled to the optimum power ratio of 60 ~ 80%. And the BESS SOC range is controlled by setting the average value of 42.5%by using the analysis result. The simulation scenarios are designed based on the comparison of renewable energy power supply and power demand. Also, the application of the diesel generator efficiency and BESS SOC setting characteristics are also reflected. Thus, a total of 12 scenarios are constructed. As a result of simulation, it is verified that the fuel consumption of the diesel generator is minimized and the maximum energy of the BESS is obtained after the algorithm proposed in this paper is applied on it.Improvements/Applications: In future research, we will construct a virtual MG operation system, which can reflect various grid situations, characteristics of MG elements, and control and measure variables.Â Â
Keywords: semi-wheel system; microgrid; pre-validation; BESS; diesel Generator; virtual analysis